2012
DOI: 10.1371/journal.pone.0048067
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Angiogenic Cells can be Derived from Cryopreserved Peripheral Blood Mononuclear Cells

Abstract: BackgroundCell transplantation for regenerative medicine has become an appealing therapeutic method; however, stem and progenitor cells are not always freshly available. Cryopreservation offers a way to freeze cells as they are generated, for storage and transport until required for therapy. This study was performed to assess the feasibility of cryopreserving peripheral blood mononuclear cells (PBMCs) for the subsequent in vitro generation of their derived therapeutic population, circulating angiogenic cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In line with our findings previous studies have already reported that cryopreservation can rather influence activation status than frequency or function of mononuclear cells. In particular, human T-cells, monocytes or circulating angiogenic cells can be thawed without considerable alteration of their phenotype and function [13] [15] . Cryopreservation is also routinely used for storage of autologous CD34 + cells suggesting that cryopreserved blood cells usually match fine fresh cells [16] .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings previous studies have already reported that cryopreservation can rather influence activation status than frequency or function of mononuclear cells. In particular, human T-cells, monocytes or circulating angiogenic cells can be thawed without considerable alteration of their phenotype and function [13] [15] . Cryopreservation is also routinely used for storage of autologous CD34 + cells suggesting that cryopreserved blood cells usually match fine fresh cells [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The low temperatures allow the cells to enter a quiescent state in which cellular functions are suspended without affecting their intrinsic characteristics (1). Peripheral blood mononuclear cells (PBMCs) are frequently cryopreserved for use in transplants or immunological studies (2,3). However, the cryopreservation process may affect viability, phenotype, and cellular functionality due to factors such as inadequate temperatures, the freezing protocol used, the expertise of the personnel, and freezing time (4,5).…”
mentioning
confidence: 99%
“…All tissue samples were sectioned and randomly allocated to immediate cell culture (fresh tissue), immediate cryopreservation or delayed cryopreservation after 24 hours of refrigeration (4°C) in cardioplegia solution (lactated ringers, 2% St Thomas solution, 5 mEq NaHCO3 and 10 mEq KCl; Thermo Fisher Scientific). Tissue samples were cryopreserved to -80°C within 5% dimethyl sulfoxide, 6% fetal bovine serum within Iscove’s Modified Dulbecco’s Medium [ 9 ]. One month later, cryopreserved tissue specimen vials were recovered in a 37°C water bath prior to processing.…”
Section: Methodsmentioning
confidence: 99%